Withaferin A Induces Proteasome Inhibition, Endoplasmic Reticulum Stress, the Heat Shock Response and Acquisition of Thermotolerance - Khan, Saad (Public Library of Science, 2012)
In the present study, withaferin A (WA), a steroidal lactone with anti-inflammatory and anti-tumor properties, inhibited proteasome activity and induced endoplasmic reticulum (ER) and cytoplasmic HSP accumulation in Xenopus laevis A6 kidney epithelial cells. Proteasomal inhibition by WA was indicated by an accumulation of ubiquitinated protein and a decrease in chymotrypsin-like activity. Additionally, immunoblot analysis revealed that treatment of cells with WA induced the accumulation of HSPs including ER chaperones, BiP and GRP94, as well as cytoplasmic/nuclear HSPs, HSP70 and HSP30. Furthermore, WA-induced an increase in the relative levels of the protein kinase, Akt, while the levels of actin were unchanged compared to control. Northern blot experiments determined that WA induced an accumulation in bip, hsp70 and hsp30 mRNA but not eIF-1α mRNA. Interestingly, WA acted synergistically with mild heat shock to enhance HSP70 and HSP30 accumulation to a greater extent than the sum of both stressors individually. This latter phenomenon was not observed with BiP or GRP94. Immunocytochemical analysis indicated that WA-induced BiP accumulation occurred mainly in the perinuclear region in a punctate pattern, while HSP30 accumulation occurred primarily in a granular pattern in the cytoplasm with some staining in the nucleus. Prolonged exposure to WA resulted in disorganization of the F-actin cytoskeleton as well as the production of relatively large HSP30 staining structures that co-localized with F-actin. Finally, prior exposure of cells to WA treatment, which induced the accumulation of HSPs conferred a state of thermal protection since it protected the F-actin cytoskeleton against a subsequent cytotoxic thermal challenge.